Improving Students’ Vocabulary Achievement through Make a Match Method - Bintari, Bintari; Supiah, Supiah (EEdJ: English Education Journal, 2023)
Developing students’ vocabulary achievement using Make a Match Method in recount text is the main purpose of this study. A quantitative research methodology was implemented with quasi-experimental design. The sample of the study were eight grade students of a public junior high school in Puding Besar, Bangka Belitung. They were taken from two classes which consisted of 44 students. This study was conducted by using purposive sampling technique with test as the instrument. The seekings indicated that the average score of experimental and control group post-test differed 7,87 points. Moreover, the calculation of the independent sample test of experimental and control group revealed that the t-obtained in equal variences assumed was 4.814 and the significant (2-tailed) was.000. it can be inferred that there was a significant difference amongst those two samples as the result of the t-obtained was higher than t-table (4.814˃2.02) and the significant (2-tailed) was more modest than calculation with level significant (.000˂0.05). In other words, Make a Match Method enhanced the students’ vocabulary achievement. Ability to develop the English teaching and learning activity was the expected contribution for this study.